Indonesian and Malaysian Palm Oil Exports Encountered Uncertainty in International Trade Amid the COVID-19 Pandemic - Rumbiati Rumbiati; Hanif Saputra Affandi (Universitas Bangka Belitung, 2026)
This paper analyzes the export performance of Indonesia and Malaysia in global, Chinese, and Indian markets during the uncertain global trade caused by the pandemic. The RCA index was utilized to evaluate the level of competitiveness, while the CMS analysis helped determine the key drivers behind the growth of palm oil exports. Although there was a downward trend overall, Indonesia maintained a higher degree of competitiveness compared to Malaysia in both the global and Chinese markets. An interesting observation is the decline in Indonesia's RCA index value from 2019 to 2021, despite an increasing trend in export market share during the pandemic. The CMS analysis indicates that Indonesia and Malaysia benefited from positive effects in terms of global export growth and commodities. This shows that both countries successfully adapted to global market challenges, particularly regarding environmental sustainability. However, Indonesia showed positive competitiveness effect values in both periods, while Malaysia had negative values. This suggests that Indonesia increased its market share during that period while Malaysia experienced a decline in market share. The implications of these findings highlight the urgent necessity for both governments to fortify downstream industrial policies, ensure strict compliance with environmental sustainability standards, and adapt to shifting global market preferences to sustain long-term competitive advantages